Metodologia para análise de custos da indisponibilidade de transformadores de potência em subestações - Campanhola, Filipe Possatti (2018)
Brazil has one of the largest energy generation and transmission systems in the world, with continental dimensions, consisting of a nearly interconnected system. Currently, more than 98% of national power generation and transmission is connected to the National Interconnected System - SIN, responsible for achieving a better distribution between an energy supply and demand in the country, ensuring the supply and controlling the level of the hydroelectric reservoirs, as well as generating energy from other sources. Electric power transmission systems are basically composed of two parts, as transmission lines and as substations, the substations have as their most costly component the power transformer, representing about 60% of the value of the substation. Due to the aging of these equipments, it is necessary to create methodologies that assist as energy concessions in the decision making on a replacement of these equipments. In this context, this dissertation had the objective of proposing a methodology to analyze the costs generated by power transformer shutdowns in substations, both for programmed shutdowns and for others. This cost wad calculated through cost due to the variable portion and costs generated by equipment life reduction. The methodology was tested in the CEEE-GT area, 240 shutdowns of 69 sets of real transformers installed in the extreme south of Brazil were analyzed over a period of 5 years. The results showed that the average values related to the variable portion exceeded R$ 17,000.00 per unit while the values referring to the anticipation of the replacement reached values of up to R$ 50,000.00 per unit. The total cost of unavailability reached R$ 1,338,575.75, showing the importance of analyzing these costs.